2016
DOI: 10.1002/14651858.cd012085
|View full text |Cite
|
Sign up to set email alerts
|

Motor control exercise for acute non-specific low back pain

Abstract: We identified only three small trials that also evaluated different comparisons; therefore, no firm conclusions can be drawn on the effectiveness of MCE for acute LBP. Evidence of very low to moderate quality indicates that MCE showed no benefit over spinal manipulative therapy, other forms of exercise or medical treatment in decreasing pain and disability among patients with acute and subacute low back pain. Whether MCE can prevent recurrences of LBP remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 179 publications
1
45
0
4
Order By: Relevance
“… 21 We will consider studies in which MCE is described as motor control, core stability or a specific stabilisation exercise and/or the study describes exercise aiming to facilitate, activate, restore, train or improve the function of the deep musculature of the spine. 27 43 All these different names of MCEs will be used in our search syntax. In addition, we will include trials evaluating Pilates, because the principles of Pilates may overlap with the principles of a motor control intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 We will consider studies in which MCE is described as motor control, core stability or a specific stabilisation exercise and/or the study describes exercise aiming to facilitate, activate, restore, train or improve the function of the deep musculature of the spine. 27 43 All these different names of MCEs will be used in our search syntax. In addition, we will include trials evaluating Pilates, because the principles of Pilates may overlap with the principles of a motor control intervention.…”
Section: Methodsmentioning
confidence: 99%
“… 44 It is important that all the studies included focus on specific muscle activity in their training programme and if a trial consists of specific stabilisation without consideration of specific muscle activity it will be excluded. 43 Furthermore, when MCEs are used in addition to other treatments in primary studies, they need to represent at least 50% of the total treatment programme to be included. 27 …”
Section: Methodsmentioning
confidence: 99%
“…Further, a previous work has shown no differences in outcome between a subgroup of patients with LBP who responded positively and negatively to a clinical prediction rule for manual therapy (Hancock, Maher, Latimer, Herbert, & McAuley, ). Similarly, Cochrane and systematic reviews (Macedo et al, ; Saragiotto et al, ; Smith, Littlewood, May, ) have reported no concrete evidence for the effectiveness of stabilization exercises in patients suffering from acute LBP. This we hypothesize to the mechanical nature of symptoms displayed by the patients at baseline that lead to the classification.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk stabilization exercises are one of the important components of rehabilitation training for increasing trunk muscle activation [1] because it is possible to re-educate the trunk muscles for proper activation and coordination through improved exercise control, and they can lead to improvement of vertebral stability [2,3]. It also maintains spinal alignment, provides adequate motion control for functional activity, and is widely used to prevent and treat back pain [4].…”
Section: Introductionmentioning
confidence: 99%